Co-infections by Mycoplasma hyopneumoniae, Mycoplasma hyorhinis and Mycoplasma flocculare in macroscopic lesions of lung consolidation of pigs at slaughter - Ferreira, Marcela Manduca [UNESP]; Mechler-Dreibi, Marina Lopes [UNESP]; Sonalio, Karina [UNESP]; Almeida, Henrique Meiroz de Souza [UNESP]; Ferraz, Maria Eugênia Silveira [UNESP]; Jacintho, Ana Paula Prudente [UNESP]; Maes, Dominiek; de Oliveira, Luís Guilherme [UNESP] (Elsevier, 2021)
Infections with Mycoplasma hyopneumoniae (Mhyo), Mycoplasma hyorhinis (Mhr) and Mycoplasma flocculare (Mfloc) are common in swine. However, the degree of co-infections and the correlations between these mycoplasma co-infection and the severity of macroscopic lung consolidation lesions (MLCL) have not yet been explored in Brazil.The objectives were to quantify Mhyo, Mhr, and Mfloc in MLCL of slaughter pigs in Brazil, and to assess correlations with the degree of MLCL in slaughter pigs. To this end, five groups of lungs were made based on severity of lung lesions, and 80 lungs were collected for each group (400 lungs in total). The Mycoplasmas were quantified using a multiplex qPCR. Statistical differences and comparison between the groups were evaluated, respectively, by the Kruskal-Wallis test (p < 0.05) and Dunn's test (p < 0.05), and the correlation between the data was performed by Spearman's method (p < 0.05). The results revealed that the extent of MLCL showed a positive correlation with the Mhyo estimate (rho = 0.26; p < 0.05), a negative correlation with the Mfloc estimate (rho= -0.15; p < 0.05), and no significant correlation with the Mhr estimate (p = 0, 12). The extension of MLCL showed a positive correlation with the co-infection by Mfloc and Mhr (rho = 0.17; p < 0.05), and no significant correlation with Mhyo and Mhr (p = 0.87), and a negative correlation with Mhyo and Mfloc (rho= -0.28; p < 0.05). This study allowed to infer that, regarding the extension of MLCL, Mhr and Mfloc did not present opportunistic activity in relation to primary infection by Mhyo, but revealed some potential aggravation of these lesions. In addition, Mhyo expressed inhibitory behavior towards Mfloc, suggesting that one can compete with the other's presence.
Keywords: Mollicutes; Pigs; Porcine enzootic pneumonia; Respiratory diseases